2006
DOI: 10.1002/app.24839
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyether‐based polyurethane dolomite composite

Abstract: A polyether polyol-based two-component polyurethane composite was prepared by a reaction of polypropylene glycol (PPG) and diethylene glycol (DEG) used as a crosslinker. The final reaction for the preparation of composite is carried out with processed polyether polyol and diphenylmethane 4,4 0 -diisocyanate (MDI). The physicochemical properties of processed polyether polyol have been measured, such as viscosity, moisture content, and hydroxyl value. The composite has been formed with loading of inorganic fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Similar results were reported by previous researchers working on polymer/dolomite composites, whereby the elongation of break decreased with increasing dolomite content. 9,12 Figure 5: Elongation at break of PBT and PBT/dolomite composites.…”
Section: Flexural Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were reported by previous researchers working on polymer/dolomite composites, whereby the elongation of break decreased with increasing dolomite content. 9,12 Figure 5: Elongation at break of PBT and PBT/dolomite composites.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…Several researchers have reported studies on the effect of dolomite on mechanical properties of polymers. [9][10][11][12] Ali et al reported that dolomite increased the compressive strength of polyester-based polyurethane composites. 9 Another study reported that dolomite enhanced the modulus and hardness of polyester/ dolomite composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu yüzden, bu özelliklerin iyileştirilmesi üzerine çalışmalar devam etmektedir. Bu malzemelerin ısıl bozunma ve yanma dirençlerinin artırılması için uygulanan yöntemler arasında, farklı alev geciktiriciler [1][2][3][4][5] ve dolgu maddelerinin [6][7][8][9][10][11] ilavesi önemli bir yer tutmaktadır. Malzemelerin ısıl bozunma ve yanma direnci artırılırken, ısı iletim katsayısı ve mekanik özelliklerindeki değişimlerin de incelemeye alınması gerekmektedir [12,13].…”
Section: Gi̇ri̇ş (Introduction)unclassified